2017
DOI: 10.1039/c6py01995a
|View full text |Cite
|
Sign up to set email alerts
|

Conformation pre-organization in fluorene-based conjugated polymer for simultaneous enhancement of luminescence and charge mobility

Abstract: The simultaneous enhancement of emission efficiency and charge mobility is realized by poor solvent induced conformation complanation in fluorene-based copolymer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In the design of high-performance LCPs, an effective method for suppressing chain aggregation in the solid state is to isolate the backbone chains. For red and green LCPs, sufficient progress has been made over the last few decades for applications in organic light-emitting diodes (OLEDs), polymer lasers, , and thin-film transistors . However, blue LCPs that show both long-term stability and high efficiency remain a challenge due to the high energy levels and wide band-gaps. , It has been demonstrated that polyfluorenes (PFs) are promising candidates for blue-light-emitting materials, with the advantages of easy modification, deep blue emission, and high quantum efficiency. ,, However, for PFs in the solid state, a green band emission due to chain aggregation or the ketone at the C-9 position limits commercial application. Many approaches have been developed to decrease the tendency of aggregation and to avoid this detrimental excimer emission, including substitution of C-9 with bulky groups, inducing quasi-planar conformation, copolymerization with steric hindrance, and use of configurations of starburst oligomers. The planar conformation of PFs (β-phase) can also enhance the charge carrier mobility, spectral purity of the blue emission, and efficiency of the amplified spontaneous emission (ASE). , Compared to the quasi-planar conformation of chains in the robust spiro-bridged ladder-type poly­( p -phenylene), the β-phase in PFs stems from an intriguing “planar zigzag” (2 1 helix) chain conformation stabilized by the balance between interchain steric interaction and molecular aggregation in the solid state in thin films, which can induce an enhanced effective conjugation length, close molecular chain packing, and a larger Förster radius for excitation transfer. In our previous work, the β-phase in a bulky polydiarylfluorene was obtained by regulating the interplay between bulky groups using steric hindrance and between alkoxy side chains using van der Waals forces .…”
Section: Introductionmentioning
confidence: 99%
“…In the design of high-performance LCPs, an effective method for suppressing chain aggregation in the solid state is to isolate the backbone chains. For red and green LCPs, sufficient progress has been made over the last few decades for applications in organic light-emitting diodes (OLEDs), polymer lasers, , and thin-film transistors . However, blue LCPs that show both long-term stability and high efficiency remain a challenge due to the high energy levels and wide band-gaps. , It has been demonstrated that polyfluorenes (PFs) are promising candidates for blue-light-emitting materials, with the advantages of easy modification, deep blue emission, and high quantum efficiency. ,, However, for PFs in the solid state, a green band emission due to chain aggregation or the ketone at the C-9 position limits commercial application. Many approaches have been developed to decrease the tendency of aggregation and to avoid this detrimental excimer emission, including substitution of C-9 with bulky groups, inducing quasi-planar conformation, copolymerization with steric hindrance, and use of configurations of starburst oligomers. The planar conformation of PFs (β-phase) can also enhance the charge carrier mobility, spectral purity of the blue emission, and efficiency of the amplified spontaneous emission (ASE). , Compared to the quasi-planar conformation of chains in the robust spiro-bridged ladder-type poly­( p -phenylene), the β-phase in PFs stems from an intriguing “planar zigzag” (2 1 helix) chain conformation stabilized by the balance between interchain steric interaction and molecular aggregation in the solid state in thin films, which can induce an enhanced effective conjugation length, close molecular chain packing, and a larger Förster radius for excitation transfer. In our previous work, the β-phase in a bulky polydiarylfluorene was obtained by regulating the interplay between bulky groups using steric hindrance and between alkoxy side chains using van der Waals forces .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the figures, with the continuous increase in forward‐bias voltage, a gradual rise in the current density was noticed. Of course, this is characteristic of a distinctive diode 55‐58 . Further, their threshold voltages were found to be 5.06 V ( Py 1 ), 5.57 V ( Py 2 ), 5.77 V ( Py 3 ), and 4.04 V ( Py 4 ).…”
Section: Resultsmentioning
confidence: 90%